Energy-protective function of plant composition in the experimental dyslipoproteidemia - A. A. Toropova; Y. G. Razuvaeva; S. V. Lemza; S. M. Nikolaev; N. V. Verlan; A. Yu. Erentueva (Acta Biomedica Scientifica)
The influence of the plant composition on the functional state of rat hepatic mitochondria and biochemical indices of energy metabolism was studied. Experiments were carried out on 42 white Wistar rats. The application of the plant composition increases contingency between oxidation and phosphorylation, as well as coefficients of respiratory stimulation and respiratory control by 17 % (р < 0.05) and 15 % (р < 0.05) respectively as compared to the control group. The tested herbal medicine increases the ATP content by 29 % (р < 0.05) and improves the activity of pyruvate kinase and H+-ATPase by 1.9 and 1.2 times respectively which indicates a partial restoration of energy metabolism in hepatocytes. The results of the research allow us to recommend the plant compositionfor its further study as a potential prospective hypolipidemic remedy for non-alcoholic fatty liver disease.